Analisis Faktor Kepemimpinan Kepala Sekolah Dalam Meningkatkan Minat Baca Siswa - Rohmah Mitra; Muhammad Gamal; Nadya Kartika; Rizka Adillah; Rizki Akmalia (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This research discusses the principal leadership factors that contribute to increasing students interest in reading. Many studies have been conducted to find out how a school principal influences teacher and student performance. For example, this research aims to identify the main factors that influence the choice of principals in public elementary schools in Pekanbaru City. Other research also emphasizes the role of school principals in improving student achievement. This research can help us understand the relationship between school leaders and students' interest in reading.